Mitotic instability in benomyl-resistant transformants of a fluffy strain of Neurospora crassa - C. Rossier; G. Brazil; A. Utz-Pugin (Fungal Genetics Reports, 1992)
The isolation of the beta-tubulin gene from a benomyl-resistant Neurospora crassa strain (Orbach et al. 1986 Mol. Cell. Biol. 6:2452-2461) has provided a dominant selectable marker usable in transformation experiments with N. crassa.